Problematika Implementasi Koperasi Merah Putih dalam Penguatan Ekonomi Kerakyatan di Indonesia - Muzamzil Muzamzil; Suparto Wijoyo (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Red and White Cooperative (Koperasi Merah Putih) is a strategic government policy aimed at strengthening the people's economy through community empowerment at the village and sub-district levels. This study aims to analyze the implementation of the Red and White Cooperative as an instrument of people-centered economic development and to identify the challenges arising from its implementation within the perspective of national law. This research employs a normative legal research method using statutory and conceptual approaches. Legal materials were collected through library research, including primary, secondary, and tertiary legal sources. The findings indicate that the Red and White Cooperative plays an important role in expanding access to productive economic activities, strengthening local economic institutions, and promoting equitable welfare. However, its implementation still faces several challenges, including regulatory disharmony, overlapping authority with Village-Owned Enterprises (BUMDes), limited human resource capacity, capital constraints, and inadequate supervision mechanisms. Therefore, strengthening regulations, institutional capacity, and supervisory systems is necessary to enhance the effectiveness of the Red and White Cooperative as an instrument of people-centered economic development in Indonesia.